Polymorphisms and features of cytomegalovirus UL144 and UL146 in congenitally infected neonates with hepatic involvement. - Gangqiang Guo; Liang Zhang; Sisi Ye; Yingying Hu; Baoqing Li; Xiangwei Sun; Chenchen Mao; Jianfeng Xu; Yiping Chen; Lifang Zhang; Xiangyang Xue (PLoS ONE, 2017)
Human cytomegalovirus is a significant agent of hepatic involvement in neonates. In this study, we investigated the polymorphisms and features of the viral genes UL144 and UL146 as well as their significance to congenital hepatic involvement. In 79 neonates with congenital cytomegalovirus infection and hepatic involvement, full length UL144 and UL146 were successfully amplified in 73.42% and 60.76% of cases, respectively. Sequencing indicated that both genes were hypervariable. Notably, UL144 genotype B was highly associated with aspartate aminotransferase (P = 0.028) and lactate dehydrogenase (P = 0.046). Similarly, UL146 genotype G1 and G13 were significantly associated with CMV IgM (P = 0.026), CMV IgG (P = 0.034), alanine aminotransferase (P = 0.019), and aspartate aminotransferase (P = 0.032). In conclusion, dominant UL144 (genotype B) and UL146 (genotype G1 and G13) genotypes are associated with elevated levels of enzymes and CMV IgM and IgG of cytomegalovirus infection.